CGIAR Research Program on Livestock - Plan of Work and Budget 2020 - CGIAR Research Program on Livestock (CGIAR Research Program on Livestock, 2020)
There are no major changes to the overall Theory of Change for the CRP Livestock. However, Flagships have been working to develop individual Theories of Change to guide work carried out for each of their main product lines/areas of research. Minor changes at Flagship level include: • FP1 Livestock Genetics developed detailed theories of change for each of the main livestock breeding programs: dairy cattle in Tanzania and Ethiopia; small ruminants in Tanzania and Ethiopia; chicken in Ethiopia, Tanzania and Nigeria. This has been important in defining flagship activities for 2020. • In FP2 Livestock Health, an emphasis emerged on understanding current use of antimicrobials to design effective interventions, rather than establishing monitoring systems. • FP3 Feeds and Forages reduced the number of product lines from 15 to seven, allowing for greater focus. • In FP4 Livestock and the Environment, new focus is given to the soil health benefits of forage intensification and rangeland management and the global positioning of the research, including documenting engagement with key agendas: Global Landscape Forum, Intergovernmental Panel on Climate Change, Global Research Alliance for Greenhouse Gases.